Fault-tolerance planning in multi-radio hybrid wireless-optical broadband access networks - Correia, Noélia (2013)
The wireless-optical broadband-access network (WOBAN) architecture has been proposed as a flexible and cost-effective solution for future access networks. However, for WOBANs to provide geographically continuous wireless coverage it is necessary to integrate fault tolerance in the design of such networks. At the optical back end, multiple failures, having different impact levels, may be addressed (e.g., optical network unit, optical line terminal). At the wireless front end, the disruption of connections, or throughput speed decrease on user's devices, can be a consequence of unlicensed spectrum utilization, where the radio band is common to different systems. We address the problem of planning a fault-tolerant multiradio WOBAN while using resources efficiently. The proposed fault model is general and may be applied to any fault-tolerance scenario (e.g., some nodes/links/region only). The adopted approach is revealed to make an efficient reuse of spectrum under different fault-tolerance scenarios.